Health effects of the time-restricted eating in adults with obesity: A systematic review and meta-analysis - Chen, Weiyi; Liu, Xiaoli; Bao, Lei; Yang, Ping; Zhou, Huihui (Frontiers in Nutrition, 2023)
Background: The number of people suffering from overweight or obesity has been steadily increasing in recent years. As a new form of diet, the efficacy of Time-restricted eating (TRE) remains debatable. Objective: This meta-analysis quantified the effect of TRE on weight change and other physical parameters in obese and overweight adults. Method: We did a systematic review and meta-analysis of RCTs comparing the TRE interventions on weight loss and other metabolic parameters by searching PubMed, Embase, and Cochrane Central Register of Controlled Trials to identify eligible trials published from database inception up until August 23, 2022. The risk of bias was assessed using the Revised Cochrane risk-of-bias tool (ROB-2.0). Meta-analysis was performed using Review Manager 5.4.1 software. Result: Nine randomized controlled trials with 665 individuals (345 in the TRE group while 320 in the control group) were included. Results indicated that TRE had a greater decrease in body weight (-1.28kg;95%CI [-2.05, -0.52], p=0.001), fat mass (-0.72 kg; 95%CI [-1.40, -0.03], p=0.04), body mass index (-0.34 kg/m²; 95% CI [-0.64, -0.04], p=0.03) and diastolic blood pressure (-2.26mmHg 95%CI [-4.02, -0.50], p=0.01). However, the meta-analysis demonstrated that there was no significant difference between TRE and the control group in lean mass, systolic blood pressure, waist circumference, fasting glucose, fasting insulin, HOMA-IR, total cholesterol, high-density lipoprotein, low-density lipoprotein, and triglycerides. Besides, the duration of the study and daily eating window also had an impact on weight change. Conclusion: TRE was associated with reductions in weight and fat mass and can be a dietary intervention option for adults with obesity. But high-quality trials and longer follow-ups are needed to draw definitive conclusions.